Kehidupan Ekstraterestrial dalam Perspektif Al-Qur’an dan Sains (Kajian Tafsir Tematik) - Rijal Alfaruq; Harapan Siregar; M. Febri Rahmadiah; Edi Hermanto; Ridhoni Putra Panginra (Jurnal Pustaka Cendekia Hukum dan Ilmu Sosial, 2025)
This research discusses of extraterrestrial life from the perspective of the qur’an and science using analysis method Maudhu’i. The Qur'an is a miracle that is eternal and scientific in nature that actually invites each reader to discuss, study, and research the verses in order to find the nature of science. The questions that will be examined in this thesis are about: (1) What is the nterpretation of the qur’an verse about extraterrestrial life according to the mufassir? (2) How does science view extraterrestrial life? To answer the above problem the researcher used the type of literature research, then analyzed descriptively based on the interpretation of verses related extraterrestrial life using analysis method Maudhu’i the primary source is the book of Scientific Interpretation the existence of life in the universe from the perspective of the qur’an and science and smart science book in the qur’an and its secondary data include books, journals related to this research. The qur’an give a hint in surah as-syura verse 29 whit theword dabbah which mean creeping creatures that exist on earth an in the sky. The theory used in this study is conceptual thematic by explaining scientific meanings that are not mentioned in the Qur'an literally well as astrobilogy theory on understanding the dabbah theme in the qur’an. The result of this research is (1) relevance between the qur’an and science about extraterrestrial life. This is demonstrated by the discovery or microorganisms on mars and water on the planets of the solar system. (2) Surah al-anbiya verse 30 states that water is the main source of formation of life, the the discovery water on the planets Mars and Uranus is proof there is no contradiction between science and the qur’an.